Technostress and its Impact on the Job Performance of Teachers - Valiao, Adryan (Journal of Interdisciplinary Perspectives, 2025)
In the context of rapid technological advancements and challenges posed by the COVID-19 pandemic, this study investigates the impact of technostress on the job satisfaction and performance of 100 faculty members from a private higher education institution in Bacolod City. Using a descriptive survey research design, data were collected through a structured questionnaire. The study examined five dimensions of technostress: Techno-Overload, Techno-Complexity, Techno-Insecurity, Techno-Invasion, and Techno-Uncertainty. Results showed that despite experiencing high levels of technostress, faculty members reported very high job satisfaction and perceived improved performance due to integrating technology into their teaching practices. Analysis revealed no significant differences in technostress levels, job satisfaction, or performance based on sex, teaching experience, or department, highlighting a shared experience across all demographics. The study emphasizes the resilience of faculty in adapting to rapid technological changes, showcasing their ability to maintain high levels of job satisfaction and performance amidst the challenges of digital transformation. However, it recommends targeted institutional strategies, such as regular training, enhanced technological support, and stress management programs, to mitigate the effects of technostress and sustain high levels of satisfaction and performance. These findings underline the importance of proactive measures to support educators in a digitally intensive educational landscape, ensuring their well-being and long-term professional development.